Capacitive touch panel with low sensitivity to water drop employing mutual-coupling electrical field shaping technique - Zhong, Longjie (2021)
This paper proposes a novel method to reduce the water interference on the touch panel based on mutual-capacitance sensing in human finger detection. As the height of a finger (height >10 mm) is far larger than that of a water-drop (height <1 mm), if the density distribution of electrical field of the touch panel's sensing cell is high in the high-height space (height >10 mm) and low in the low-height space (height <1 mm), the sensing cell can be designed to distinguish the finger from the water-drop. To achieve this density distribution of the electrical field, the mutual-coupling electrical field shaping (MEFS) technique is employed to build the sensing cell. The drawback of the MEFS sensing cell is large parasitic capacitance, which can be overcome by a readout IC with low sensitivity to parasitic capacitance. Experiments show that the output of the IC with the MEFS sensing cell is 1.11 V when the sensing cell is touched by the water-drop and 1.23 V when the sensing cell is touched by the finger, respectively. In contrast, the output of the IC with the traditional sensing cell is 1.32 and 1.33 V when the sensing cell is touched by the water-drop and the finger, respectively. This demonstrates that the MEFS sensing cell can better distinguish the finger from the water-drop than the traditional sensing cell does.